Allelopathic potential of secondary metabolites produced by Alternaria brassicicola and physiological mechanisms on Amaranthus tricolor - Manichart, N.; Somala, N.; Laosinwattana, C. (My University, 2023)
The results revealed that all isolated fungal strains significantly reduced germination and early growth of amaranth compared to control. The original metabolites (1.00X) from the fungus coded UNK03, which was identified as a strain of Alternaria brassicicola (98.44% similarity, accession number LC440588.1), showed the highest inhibition rate and suppressed with the maximum inhibitory level (78.75%) compared to control. In a similar pattern, the growth of the tested plant was significantly reduced by the cultural filtrates by 70.45% and 89.38% in shoot and root, respectively. Based on efficacy in the seed bioassay, the A. brassicicola metabolites (CF03) were selected for exposure with the tested seed to determine the mechanism of action (MOA). The results show that the A. brassicicola metabolites inhibited seed imbibition and -amylase activity of the tested seed with dose-dependent effects, strongly suggesting the potential of the metabolites to inhibit seed germination and seedling growth. Therefore, this work indicates that the fungal metabolites contain potent herbicidal compounds that can potentially be used to control A. tricolor.
Keywords: Alternaria brassicicola; Herbicidal activity; Mechanism of action (MOA)